Meso-structured organosilicas as fillers for Nafion (R) membranes - Rosero-Navarro, Nataly C. y
The processing and characterization of composite membranes casted from commercial Nafion (R) suspension with incorporation of benzene-bridged periodic mesoporous organo-silicas functionalised with sulfonic acid groups (S-Ph-PMO) are presented in the search for improved protonic conductivity under low humidity conditions. It is shown that the incorporation of 10 wt%S-Ph-PMO fillers into Nafion (R) improves the proton conductivity by approximately 70%, with the composite membranes reaching 0.19 S . cm(-1) in 98% relative humidity (RH), or 0.05 S . cm(-1) in 60% RH, at 94 degrees C. The filler effect on the conductivity increases at low RH, representing an enhancement of similar to 250% and similar to 425% with respect to the conductivity of Nafion (R) at 40% RH and 20% RH, respectively. The conductivity improvement is also higher at low temperature due to the higher activation energy of Nafion (R). Such effects are interpreted by the high proton mobility in the stable mesoporous channels of the fillers. (C) 2013 Elsevier B.V. All rights reserved.